Pengaruh Good Corporate Governance terhadap Kinerja Keuangan Perbankan yang terdaftar di BEI periode 2019-2023 - Rahmaita, Adiah syafithree, (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2024)
This research aims to determine the effect of implementing good corporate governance on the financial performance of banks listed on the IDX for the 2019-2023 period. This research uses a quantitative descriptive approach. The data used is secondary data from the annual reports of banking companies listed on the IDX. The sampling technique in this research was 42 banking companies. The research results show that the Board of Commissioners and Audit Committee do not have a significant effect on banking financial performance. Meanwhile, the Board of Directors and Institutional Ownership have a significant influence on Banking Financial Performance.